Profil kasus batu empedu di RSUP Prof. Dr. R. D. Kandou Manado periode Oktober 2015-Oktober 2016 - Tuuk, Andreyne L.Z.; Panelewen, Jimmy; Noersasongko, A. Djarot (Universitas Sam Ratulangi, 2016)
Abstract: Gallstones are solid materials or crystals formed in gallbladder, common bile duct, or in both. Gallstones constitute a significant health problem in developed countries. Epidemiologic studies showed that increasing age was associated with increasing prevalence of gallstones. This study was aimed to obtain the profile of gallstone cases at Prof. Dr. R. D. Kandou Hospital from October 2015 to October 2016. This was a retrospective descriptive study. The results showed that there were 113 cases of gallstones. The majority of cases were females, age group 60 years, serum bilirubin â‰¥3 mg/dl associated with apparent jaundice, and treated with surgery using cholecystectomy laparotomy and cholecystectomy laparoscopy techniques.Keywords: gallstone, profileÂ Abstrak: Batu empedu adalah material atau kristal yang terbentuk dalam di dalam kandung empedu, saluran empedu, atau keduanya. Batu empedu merupakan masalah kesehatan yang signifikan dalam masyarakat berkembang. Studi epidemiologi menunjukkan bahwa prevalensi batu empedu berkaitan dengan meningkatnya usia dan lebih sering ditemukan pada perempuan. Penelitian ini bertujuan untuk mengetahui profil pasien batu empedu di RSUP Prof. Dr. R. D. Kandou Manado dalam periode Oktober 2015 - October 2016. Jenis penelitian ialah deskriptif retrospektif. Hasil penelitian mendapatkan 113 kasus penyakit batu empedu, Majoritas kasus ialah perempuoan, kelompok usia 60 tahun, kadar bilirubin â‰¥3 mg/dl disertai ikterik yang jelas, dengan penanganan operatif kolesistektomi laparatomi dan kolesistektomi laparoskopik. Kata kunci: batu empedu, profil